Pests and Diseases Management of Konjac (Amorphophallus muelleri Blume) - Siti Hardiyanti; Supriadi Supriadi; Sri Rahayuningsih; Titiek Yulianti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Amorphophallus oncophyllus Prain ex Hook. f. synonym A. muelleri Blume is the main source of glucomannan that is used as a food additive and dietary supplement. The crop has become a favorite in several parts of Indonesia. The plant has been known to have several pests and diseases that can cause significant losses. This review aims to highlight the importance of pests and diseases of konjac and its control strategy. Several pests and diseases attacking the konjac plant have been identified, such as mealybug, scale insect, dry and soft root, collar rot, bacterial blight, leaf spot, and mosaic. The majority of them are seeds or soil born and could be carried from the field to storage. Understanding the causal agents and their ecology is critical in formulating integrated pest management (IPM). Cultivating healthy seeds and mixed cropping with nonhost food crops (maize and rice), or as a second crop under estates’ and industrial forests’ conditions, as well as biological control, are the most applicable IPM. No specific regulation has been formulated for minimizing pests and diseases of konjac; however, it could adopt general protocol from other crops, such as taro (Colocasia esculenta) in India.